Effects of Electron-Donor and Counter-Cation in Photoinduced Deboronative and Decarboxylative Aryl Radical Generation Using Two-Molecule Photoredox Catalysts - Hashimoto, Ryoga; Furutani, Toshiki; Suzuki, Hirotsugu; Yoshimi, Yasuharu (Synlett, 2023)
In this study, we investigated the effects of electron-donors and counter-cations on the visible-light-induced deboronation and decarboxylation of arylboronic acid derivatives and benzoic acids using two-molecule photoredox catalysts. Different efficiencies in aryl radical generation were observed upon replacing the electron-donor and counter-cation. The rate of photoinduced deboronation of arylboronic acid derivatives strongly depends on the substituent, whereas the influence of counter-cation (Na+ and K+) was relatively minor. In the case of the benzoate ion derived from benzoic acid, the effect of both substituent and counter-cation decreases because of the complex mechanism. Additionally, the dependence of the oxidation ability of the radical cation on the electron-donor suggests the possibility of roughly estimating the oxidation potentials of the arylborate and benzoate ions.
Keywords: two-molecule photoredox catalyst; effect of electron-donor; effect of counter-cation; photoinduced deboronation; photoinduced decarboxylation; aryl radical; arylboronic acid ester; benzoic acid